Mapping Of Transcriptional Start Site And The Identification Of Novel Srna In Mycobacterium tuberculosis H37Rv - Lee, Li Pin (2016)
The adaptability of Mycobacterium tuberculosis (Mtb) to various environmental changes presented by host immune systems enables its persistence within infected hosts for decades. Various aspects of gene expression regulation in response to environmental stress have been extensively analyzed in Mtb. However, the roles of transcriptional start sites (TSSs) and the small regulatory RNAs (sRNAs) in regulating gene expression within Mtb are given very little attention, particularly under stress condition. This ignites the effort to map TSSs and identify sRNAs involved in different stress environments.